Post traumatic headache (PTH) in a cohort of UK compensation claimants. (April 2019) - Lane, Russell; Davies, Paul
Aim: To explore post traumatic headache characteristics and risk factors in compensation claimants by observational retrospective cohort analysis. Case results: Medicolegal reports on 116 consecutive compensation claimants aged 41.9 ± 15.0 years were reviewed 21 ± 14 months after injury. Eighty eight had suffered head and neck injuries, 21 reported only neck injury and seven had "other injuries". Ninety four percent of the head injuries were "mild". The incidence of post traumatic headache following neck injury did not differ from that following head and neck injury, and none of the "other injuries" cases developed post traumatic headache. We anticipated that all head and neck injury claimants would seek compensation for post traumatic headache, but 25% denied developing headache. Post traumatic headache was very strongly correlated with a past history of primary headache ( p  < 0.0001) but no other risk factors were identified. Post traumatic headache semiology was consistent with "migraine" or "probable migraine" in 90% of cases. Headache resolved in 30% of claimants between 3 and 24 months after injury but 70% continued to suffer headaches at the time of assessment. Forty one percent of claimants had received no treatment for post traumatic headache in primary care. Conclusions: Our data suggest that post traumatic headache is essentially "migraine" provoked by head or neck concussion. It is not clear why so many post traumatic headache sufferers receive poor or inadequate treatment for this condition.